Part X – October 1968 - Papers - The Elongation of Superplastic Alloys - W. B. Morrison (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
The principal factors influencing the total percent elongation of a lead-tin eutectic and several low-alloy steels which exhibit superplasticity were investigated. These factors are: a) Strain-rate sensitivity of the stress (m). b) Specimen geometry; in particular, diameter-to-length ratio (d0/l0), and surface irregularity (e.g. notches). A feature of the tensile deformation of a superplastic alloy is the early appearance of a neck which continues to extend throughout the test. As a result the total elongation is directly related to the diameter-to-gage-length ratio. The strain-rate sensitivity of the stress varies during extension, mainly because of microstruc-tural changes. A satisfactory correlation exists between the minimum strain-rate sensitivity and total elongation, as indicated in the equation shown below. Notches cause a considerable reduction in total elongation and their effect is greatest at high values of strain-rate sensitivity. An initial notch depth exists below which there is no appreciable effect on elongation. An equation relating elongation to strain-rate sensitivity and specimen geometry is proposed, THE total percent elongation of a tensile specimen is usually regarded as a measure of superplasticity. However, little attention has been given to the fact that total elongation is also a function of specimen diameter and gage length, even though the importance of geometry has long been recognized in the tensile testing of materials in which elongations are relatively small.* In the present study, the effect on superplas- tic extension of the ratio of specimen diameter to length was investigated and an analysis was made of strain distribution along the gage length. Superplastic alloys are characterized by having a flow stress sensitive to strain rate but relatively insensitive to strain.2"' In an earlier study,5 it was found that the strain-rate sensitivity of several low-alloy steels changed during the test and that the minimum value correlated best with total elongation. In the present study, the variation of strain-rate sensitivity during the straining of a lead-tin alloy was investigated. EXPERIMENTAL PROCEDURE Lead-tin eutectic alloy (32 pct Pb 68 pct Sn), made from high-purity lead and tin, was cast in the form of 1-in. diam rod. The rod was cold-rolled in stages to 0.25 in. diam and then swaged to 0.125 in. diam. Samples were cut from the rod at various stages of the mechanical working process. Tensile test specimens were then made by attaching threaded steel ends to the rods by an epoxy-base thermosetting adhesive which required a setting treatment of 2 days at room temperature. The rods were seated in the steel ends in holes approximately 0.01 in. oversize. The test pieces thus made were of various diameters and gage lengths. These were stored at a temperature of about -70°C (-94°F) until required for testing. The distribution of strain along the gage length of a specimen was determined at various stages of the tensile test. The lead-tin alloy was superplastic at room temperature and direct observations during testing were simple. The gage length was divided by reference marks into five initially equal units. These reference marks were made with ink and were reinforced during the test when the initial marks became faint. Photographs were taken, at intervals, of the deforming specimen and measurements of the elongation in each of the gage units were made on these photographs. Tests were also done on several superplastic low-alloy steels whose properties were described earlier.5 The chemical compositions of these steels are given in Table I. A diagram of the notched tensile specimen used in the steel tests is shown in Fig. 1. The specimens were tested at 900°C (1650°F) in a furnace through which a mixture of He + 2 pct H was continuously circulated.5 RESULTS Strain Distribution. Approximately 20 tests on lead-tin alloy specimens were conducted to determine the strain distribution during the test. An example is shown in Fig. 2 of the strain distribution in the gage